2015
DOI: 10.1111/eve.12394
|View full text |Cite
|
Sign up to set email alerts
|

Equine tapeworm infections: Disease, diagnosis and control

Abstract: Summary Equine tapeworm infection has gained increasing attention over the past few decades and a number of research studies have already been published. These focus primarily on the most common of the 3 tapeworm species, Anoplocephala perfoliata, although some new information has also been generated for the other two species, Anoplocephala magna and Anoplocephaloides mamillana. The preponderance of research studies have focused on development and validation of diagnostic techniques for tapeworm detection and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 66 publications
1
30
0
Order By: Relevance
“…The prevalence of A. perfoliata reported here is in accordance with a previous Swedish case-control study that showed positive samples in 13% (18/134) of horses [11]. Previous studies have shown conflicting results regarding the association of tapeworm infection and general colic [7]. However, A. perfoliata has consistently shown to be associated with ileocecal lesions [8,10,[45][46][47][48][49].…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence of A. perfoliata reported here is in accordance with a previous Swedish case-control study that showed positive samples in 13% (18/134) of horses [11]. Previous studies have shown conflicting results regarding the association of tapeworm infection and general colic [7]. However, A. perfoliata has consistently shown to be associated with ileocecal lesions [8,10,[45][46][47][48][49].…”
Section: Discussionsupporting
confidence: 89%
“…In comparison, coprological diagnosis of Anoplocephala infection is highly variable, in part due to the sporadic release of tapeworm eggs, poor distribution of eggs in faeces, the FEC technique used and the burden present . Modified FEC methods, such as the centrifugation/flotation technique, are most sensitive, reporting up to 61% sensitivity; however, they are more time‐consuming and labour intensive than standard methods . Sensitivity of the centrifugation/flotation technique can be increased to approximately 90% when diagnosing infections with >20 tapeworms present .…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the UK and Ireland have shown A. perfoliata to be present in 51–69% of horses examined . These parasites have been associated with colic, weight loss and colitis . Previously, frequent all‐group administration of anthelmintics was used to control equine helminths; however, interval treatment‐based practices strongly selected for anthelmintic resistance, especially in cyathostomins and P. equorum .…”
Section: Introductionmentioning
confidence: 99%
“…Less than 50% of adult horses in the UK are infected with adult tapeworms (Proudman and Trees, 1996;Lightbody et al, 2016), and many of these have subclinical infections. The risk of tapeworm-associated disease in adult horses is not well quantified (Nielsen, 2015) and colic associated with tapeworm infection appears to be relatively uncommon in most populations of adult horses (Bowen, Rendle unpublished data). Treatment should only be administered to adult horses in response to positive serum or salivary antibody testing.…”
Section: Sustainable Control Of Tapewormsmentioning
confidence: 99%